Reproductive Decision‐Making in MMR Mutation Carriers After Results Disclosure: Impact of Psychological Status in Childbearing Options. Issue 3 (22nd September 2015) - Duffour, Jacqueline; Combes, Audrey; Crapez, Evelyne; Boissière‐Michot, Florence; Bibeau, Frédéric; Senesse, Pierre; Ychou, Marc; Courraud, Julie; de Forges, Hélène; Roca, Lise
Abstract: Reproductive techniques such as prenatal diagnosis (PND) or preimplantation genetic diagnosis (PGD), although debated, are legally forbidden in France in case of Lynch syndrome. The preference of mutation carriers about their reproductive options is not systematically considered in France. We aimed to prospectively assess the reproductive preferences of mismatch repair mutation carriers consulting in our institution (2003–2010, n =  100). We also considered the short‐ and long‐term post‐disclosure psychological impact using the Impact of Events Scale‐Revised questionnaire to measure the prevalence of posttraumatic stress disorder (PTSD) in those patients. Complete data were obtained for 34 respondents (17 males, 17 females, median age of 33.5 years [22–59]). Seventeen respondents (57 %) preferred spontaneous natural conception versus 28 % and 35 % choosing PND and PGD, respectively. At results disclosure, respondents mainly explained their distress by fear of premature death (43 %) and transmitting mutated genes (42 %). One year later, this last fear remained predominant in 55 % of subjects. None of the main socio‐demographical, psychological or medical variables (including fear of transmitting mutations) was significantly associated with the reproductive preferences. Results disclosure had a real and time‐decreasing psychological impact on mutation carriers. Reproductive techniques, expected to decrease the hereditary risk, were not significantly preferred to natural conception.